STRUCTURAL ORGANIZATION OF MULTILEVEL MEMORY SCHEMES WITH AUTOMATIC STRATEGIES FOR THE EACH GROUP OF MULTILEVEL MEMORY SCHEMES (Transport systems and technologies, 2018)
The question of building a multilevel memory circuits, their reliability, features, advantages of the scheme is based on triggers and ways of organizing, modeling and their application. Creating a basic theory of building multi-circuit memory (BFSP) and, based on the theory of building a multilevel memory circuits (BRSP) extends the current fundamentals of computer technology and provides new opportunities. They can increase the speed of adjustment algorithms functioning computer devices extend the functionality of systems, extend the existence of different levels of information processing, as well as to the simultaneous processing of total and partial information on the basis of the principle of hierarchical management software that essentially can not be done on a computer Books on devices with memory triggers.
Keywords: bahatorivnevyi memory circuits, memory scheme, method, logic elements, electronic components, machine strategy.